PERAN BAHASA MELAYU PASAI DALAM PENYEBARAN BAHASA PERSATUAN NASIONAL MELALUI LEMBAGA PENDIDIKAN AGAMA ISLAM - Miswari, Miswari (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
This article aims to analyze the development of the Malay language, particularly the Pasai Malay, which played a significant role in forming the foundation of modern Malay and contributed to the emergence of the national language, Bahasa Indonesia. Using a qualitative approach through library research, this study examines various historical and philological sources relevant to understanding the spread and influence of Pasai Malay throughout the archipelago. The collected data were analyzed descriptively and narratively, emphasizing the historical, social, and religious factors underlying the dissemination of this language. The findings indicate that there are three main reasons for the wide spread and strong influence of Pasai Malay. First, through the dissemination of religious literary works by prominent scholars such as Hamzah Fansuri, Syamsuddin al-Sumatrani, Nuruddin ar-Raniri, and Abdurrauf al-Singkili, along with their disciples, who introduced Islamic concepts in the Malay language. Second, through the use of Pasai Malay as a medium of instruction in Islamic educational institutions attended by students from various regions of the archipelago. Third, through the circulation of religious literature and translated works widely used in pesantren and Islamic learning centers, which established Pasai Malay as the primary foundation for the development of modern Malay.